Profile Of Cardiac Arrhythmia In Nepalese Population By Ambulatory Electrocardiogram Analysis - Upadhayaya, A.B.; Shah, R.K.; Regmi, P.A.; Bhattarai, T.N.; Paudel, R.R.; Shrestha, U.K.; Acharya, K.P.; Khanal, H.H.; Shrestha, D (Nepalese Heart Journal, 2004)
Effective management of Cardiac arrhythmias and conduction disturbances requires accurate identification of the specific rhythm disturbances, analysis of the clinical settings in which they occur and identification of a safe and effective endpoint of therapy. Some arrhythmias are hazardous to the patient regardless of the clinical Settings (e.g. ventricular fibrillation), where as others are hazardous because of the clinical settings (e.g. rapidly conducted atrial librillation in patient with severe coronary artery stenosis) Present study aims al determining profile of cardiac arrhythmias in patients, attending a private hospital.